Genetic Variants Related to Longer Telomere Length are Associated with Increased Risk of Renal Cell Carcinoma - Machiela, Mitchell J; Hofmann, Jonathan N; Carreras-Torres, Robert; Brown, Kevin M; Johansson, Mattias; Wang, Zhaoming; Foll, Matthieu; Li, Peng; Rothman, Nathaniel; Savage, Sharon A; Gaborieau, Valerie; McKay, James D; et al. (European urology, 2017)
BACKGROUND: Relative telomere length in peripheral blood leukocytes has been evaluated as a potential biomarker for renal cell carcinoma (RCC) risk in several studies, with conflicting findings. OBJECTIVE: We performed an analysis of genetic variants associated with leukocyte telomere length to assess the relationship between telomere length and RCC risk using Mendelian randomization, an approach unaffected by biases from temporal variability and reverse causation that might have affected earlier investigations. DESIGN, SETTING, AND PARTICIPANTS: Genotypes from nine telomere length-associated variants for 10 784 cases and 20 406 cancer-free controls from six genome-wide association studies (GWAS) of RCC were aggregated into a weighted genetic risk score (GRS) predictive of leukocyte telomere length. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Odds ratios (ORs) relating the GRS and RCC risk were computed in individual GWAS datasets and combined by meta-analysis. RESULTS AND LIMITATIONS: Longer genetically inferred telomere length was associated with an increased risk of RCC (OR=2.07 per predicted kilobase increase, 95% confidence interval [CI]:=1.70-2.53, p<0.0001). As a sensitivity analysis, we excluded two telomere length variants in linkage disequilibrium (R2>0.5) with GWAS-identified RCC risk variants (rs10936599 and rs9420907) from the telomere length GRS; despite this exclusion, a statistically significant association between the GRS and RCC risk persisted (OR=1.73, 95% CI=1.36-2.21, p<0.0001). Exploratory analyses for individual histologic subtypes suggested comparable associations with the telomere length GRS for clear cell (N=5573, OR=1.93, 95% CI=1.50-2.49, p<0.0001), papillary (N=573, OR=1.96, 95% CI=1.01-3.81, p=0.046), and chromophobe RCC (N=203, OR=2.37, 95% CI=0.78-7.17, p=0.13). CONCLUSIONS: Our investigation adds to the growing body of evidence indicating some aspect of longer telomere length is important for RCC risk. PATIENT SUMMARY: Telomeres are segments of DNA at chromosome ends that maintain chromosomal stability. Our study investigated the relationship between genetic variants associated with telomere length and renal cell carcinoma risk. We found evidence suggesting individuals with inherited predisposition to longer telomere length are at increased risk of developing renal cell carcinoma.
Keywords: mendelovská randomizace; Telomere Homeostasis; odds ratio; hodnocení rizik; Phenotype; Genome-Wide Association Study; Mendelian Randomization Analysis; jednonukleotidový polymorfismus; homeostáza telomer; telomery; lidé; Telomere; Polymorphism, Single Nucleotide; karcinom z renálních buněk; genetická predispozice k nemoci; studie případů a kontrol; Risk Assessment; Genetic Predisposition to Disease; Kidney Neoplasms; leukocyty; Carcinoma, Renal Cell; Risk Factors; Case-Control Studies; Leukocytes; celogenomová asociační studie; rizikové faktory; nádory ledvin; fenotyp; Odds Ratio; Humans